Technological innovations in psychological assessment: reflections on their impact and applications in contemporary psychometrics - de la Iglesia, Guadalupe (2025)
The field of psychological assessment is undergoing a marked transition from traditional methodologies toward approaches that incorporate technological innovations, including digital platforms, serious games, chatbots, virtual reality, and artificial intelligence (AI). This article presents a review of current and emerging technological tools in psychological assessment, with particular emphasis on technology-based assessments (TBAs)—instruments that rely on digital technologies to evaluate a wide range of psychological constructs. The article describes the main types of TBAs, outlines their applications in assessing diverse psychological variables, and analyzes their growing use in psychological assessments. It highlights both the advantages and limitations of these tools and considers international guidelines for developing and implementing TBAs thatare valid, reliable, and fair. Overall, the integration of TBAs into psychological assessment represents a promising development, offering greater accessibility, increased engagement, and richer, more diverse data compared to traditional methods.